Headspace single drop microextraction for the analysis of fire accelerants in fire debris samples. - Sanagi , Mohd Marsin; Baseri , Rosriza Salisa; Ahmad, Umi Kalthom; Miskam, Mazidatulakmam; Wan Ibrahim , Wan Aini (Taylor & Francis Inc., 2010)
Fire accelerants such as gasoline, kerosene, and diesel have commonly been used in arson cases. Improved analytical methods involving the extraction of fire accelerants are necessary to increase sample yield and to reduce the number of uncertain findings. In this study, an analytical method based on headspace single drop microextraction (HS-SDME) followed by gas chromatography-flame ionization detection (GC-FID) has been developed for the analysis of simulated fire debris samples. Curtain fabric was used as the sample matrix. The optimized conditions were 2.5 mu L benzyl alcohol microdrop exposed for 20 min to the headspace of a 10 mL aqueous sample containing accelerants placed in 15-mL sample vial and stirred at 1500 rpm. The extraction method was compared with the solvent extraction method using n-hexane for the determination of fire accelerants. The HS-SDME process is driven by the concentration difference of analytes between the aqueous phases containing the analyte and the organic phase constituting the microdrop of a solvent. The limit of detection of HS-SDME for kerosene was 1.5 mu L. Overall, the HS-SDME coupled with GC-FID proved to be rapid, simple and sensitive and a good alternative method for the analysis of accelerants in fire debris samples.